Fahrplanauskunft für Dubai. Erstes intermodales Auskunftssystem im arabischen Raum. - Abdul-Reda, Liliane; Mentz, Hans-Joachim; Alefeld, Markus (Alba, 2009)
Die erste intermodale Fahrplanauskunft in arabischer Sprache ist in Dubai online gegangen. Neben dem Internetauftritt (http://wojhati.rta.ae) gibt es die Fahrplanauskunft über das Handy sowie über ein Sprachdialogsystem. Die Herausforderung in Dubai bestand darin, die speziellen Anforderungen vor Ort zu erforschen und zu berücksichtigen: Weiterhin wird in dem Artikel beschrieben, wie die Herausforderungen durch die arabische Sprache gemeistert wurden.

The first intermodal Journey Planner in arabic language is now online. It is available on the internet (http://wojhati.rta.ae) as mobile application and as speech dialog system. The challenge in Dubai was to ascertain the specific local requirements, as the diversity of population with the high amount of foreign workers, the climate, the footpath network, the map system which is still quite new and not fully completed as well as the orientation in the city. Furthermore it is described how the arabic language has been integrated.
Journey Planner for Dubai.
Keywords: Verkehr; Stadtverkehr; ÖPNV; Verkehrsunternehmen; Verkehrsmittel; Verkehrssystem; Informationssystem; Fahrgastinformation; Fahrplanauskunft